Assurance et biotechnologie - Dumont, Monique (Assurances, 1983)
In a previous edition of Assurances, the author considered the future effect of robots on certain types of manufacturing industries. Miss Dumont now looks at the expanding field of biotechnology. Miss Dumont begins by briefly defining biotechnology, and then looks at the structure of the industry and its probable future. She describes the attitude of the world of insurance, and provides us with a list of references of her sources.